Role Conflict and the Academic Department Chair - DeVaney, Thomas A; Westmoreland, Margaret B (Advances in Social Sciences Research Journal, 2025)
The academic department head or department chair in a university serves an important and complex role as an academic leader and middle manager. This study examined the role of the academic department head at one public university in the southeastern United States using a framework based on location, behavior, and expectations associated with the position. An electronic survey that included closed and open-ended items and assessed sender conflict, inter-role conflict, intra-role conflict, and workload was sent to 27 current and recent department heads. Results are based on 22 department heads who completed the electronic survey. The results indicated that department heads experienced sender conflict, inter-role conflict, and intra-role conflict. Additionally, they reported that the workload associated with the department head role was more than other academic positions that they held. Recommendations based on the results include the use of a support system to address issues such as work-life balance and mental health as well as policy revisions that create a more accurate alignment of assigned workload allocation (e.g., administration, teaching, and research and service) to actual allocation.